Democratic societies defeat (COVID-19) disasters by boosting shared knowledge - Laura Martignon; Shabnam Mousavi; Joachim Engel (Mind & Society, 2021)
Preparing people for dealing with hazards, diseases and disasters requires teaching them statistics, and ideally doing so by means of good representation formats in a dynamic fashion. Translating these dynamics to simple communication is what governments need from scientists.
Keywords: 300; COVID-19; Corona virus; Numeracy; Information representation; Policy making; Risk literacy; Democracy; Transparency